2020
DOI: 10.2176/nmc.oa.2020-0202
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Refractory Tourette Syndrome: Electrode Position and Clinical Outcome

Abstract: The efficacy of deep brain stimulation (DBS) for refractory Tourette syndrome (TS) is accepted, but whether the efficacy of DBS treatment in the Japanese population is equivalent to those reported internationally and whether adverse effects are comparable are not yet known. This study evaluated the clinical practice and outcome of DBS for TS in a Japanese institution. This study included 25 consecutive patients with refractory TS treated with thalamic centromedian-parafascicular nucleus DBS. The severity of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, no significant differences were found between different brain targets ( p > 0.05). Just recently, Kimura et al [ 96 ] reported about findings from clinical practice and outcome of DBS in TS in Japan. They included 25 patients with refractory TS treated with thalamic CM-Pf DBS.…”
Section: Review Of the Literature (Based On Search Of Studies On Dbs ...mentioning
confidence: 99%
“…However, no significant differences were found between different brain targets ( p > 0.05). Just recently, Kimura et al [ 96 ] reported about findings from clinical practice and outcome of DBS in TS in Japan. They included 25 patients with refractory TS treated with thalamic CM-Pf DBS.…”
Section: Review Of the Literature (Based On Search Of Studies On Dbs ...mentioning
confidence: 99%
“…The most common precipitating factors reported are febrile infection and discontinuation of regular medication . To our knowledge, this report is the first description of a tic status due to DBS IPG depletion …”
mentioning
confidence: 81%
“…2 To our knowledge, this report is the first description of a tic status due to DBS IPG depletion. 3 No well-established guideline for tic status management is available, but it is recommended to readminister the previously suspended drug or administer an antipsychotic in increasing dosages. In the absence of improvement, benzodiazepines can be added, and sedation may be needed in severe cases.…”
mentioning
confidence: 99%
“…Lastly, preoperative MRI was analyzed for appropriate position within the hyperintense CMT, a small nucleus measuring about 10 mm in diameter. Specific MRI sequences for stereotactic planning include the magnetization-prepared 2 rapid gradient echo [12] and fast gray matter acquisition T1 inversion recovery [13,14]. The CMT belongs to the posterior intralaminar nuclei group (including the parafascicular and central lateral nuclei), lying posterior to the hypointense mediodorsal nuclei and anterior to the hypointense pulvinar.…”
Section: Surgical Techniquementioning
confidence: 99%